THE LATEST TECHNOLOGIES AND THEIR APPLICATION IN RUSSIAN LANGUAGE LESSONS - N.A. Baratova; M.Abdujabbarova (Western European Studies, 2024)
The article discusses the use of the latest technologies in Russian language lessons, as well as their impact on the effectiveness of learning. Various approaches to the integration of digital educational platforms and technologies into the educational process are discussed
Keywords: the latest technologies; the Russian language; educational games